(untitled) (American Journal of Islam and Society, 1991)
As a general system of thought, evolutionism is the most powerful ideology in modem Western secularist civilization. It arose in the West over a century ago and spread there first, gradually reducing the Christian culture of the West until it became a residual influence. Because Western nations such as England, France, and the Soviet Union imposed themselves on Muslim lands in the form of colonialist regimes, we should not be surprised to find within the Muslim world the echoes of evolutionary thdang in many of the modernist, or Westernized, Muslims, and even amongst their opponents, the Muslim fundamentalists. This was perhaps inevitable, given that the educational system of the Muslim world has been patterned on that of the West. In the West, evolutionary modes of thought have gradually created a secularized world devoid of religious attachments. In the Muslim world, it is only natural that modernist Muslims, the so-called Westernized Muslims who take their bearings from Western as opposed to Islamic thinking, should have sought to create within Islam a similarly secularized culture, likewise cut off from its religious mots. Such Muslims have been the dominant influence in the Muslim world from the nineteenth century up to the Second World War, ample time in which to realize their ambitions. In this fashion, evolutionism, an ideology that arose in the West and succeeded in utterly de-Christianizing the West, has now penetrated into the Muslim world like a Trojan horse. That being so, we would do well to examine the origins of evolutionary thinking in the West to discern both its nature and to see how it displaced Christian beliefs and institutions. The secularist civilization it produced is now sweeping the entire globe and threatening to destroy the lingering elements of traditional Islamic civilization. By first examining what happened in the Christian world, we are in a better position to grasp what has been going on within the domains of Islam in the recent past. That understanding should have a direct bearing on the question of whether the traditional culture of Islam can be preserved. Indeed, the world of Islam may very well be the ...